Self-supporting ceramic wall system: Challenges of additive manufacturing of architectural ceramic components - Moreira, João Pedro Oliveira (2019)
The present paper analyses the use and viability of computational design and digital fabrication tools, namely ceramic additive manufacturing, to explore new possibilities on the design and manufacture of ceramic facade components. With these topics in mind, we aim to develop a prototype for a self-supporting ceramic wall system, contributing to the development of the subjects here presented and to the development of the 3D printing community. The paper focusses on objective questions such as material composition, analyzing the correct humidity percentage required to enable ceramic additive fabrication by extrusion, material retraction, analyzing its consequences and developing strategies for the connections and finally the influence of structural configuration of the components. While presenting the main challenges, we intend to draw some conclusions achieved during the design and fabrication processes.